The Analysis of the Educational Unit Assessment Strategy on the Independent Learning Curriculum at the Schools - Altaf Syauqy Iqbal Saifani; Robiatul Adawiyah (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
The Independent Learning Curriculum (ILC) is a student-centered approach emphasizing self-directed learning and individualized instruction. However, traditional assessment methods may need to align with the curriculum's goals. This paper analyzes the current strategies for assessing academic units in the ILC at the school level. A comprehensive literature review and a case study analysis were conducted to identify the current system and best practices for assessing academic units in the ILC. The literature review identified the importance of involving students in the assessment process and the need for clear learning objectives and criteria for success. The case study analysis included interviews with teachers, administrators, and students to gather data on the assessment methods and their effectiveness. The data collected from the literature review and case study analysis was then analyzed using qualitative data analysis techniques, including content and thematic analysis. The data were organized into categories and themes to identify patterns and trends in the assessment strategies used at the school level. Assessment methods were used, including self-assessment and peer and teacher assessments. It also found that involving students in the assessment process and providing clear learning objectives and criteria for success were essential factors. The paper concludes that a more comprehensive approach to assessment, which focuses on the process of learning rather than just the outcome, is necessary for a practical evaluation.